Rokok yang Menjadi Kebudayaan: Melihat Peran Pemerintah dan Agensi Lokal dalam Mengatasi Kebiasaan Merokok - Mahadika, Gilang (Jurnal Analisis Sosial Politik, 2021)
Anthropology has long history of doing research regarding tobacco. Yet, there has not been the attempts for integrating the tobacco studies. Therefore, this paper expects to reveal the historical development of tobacco utilization in general and also to understand a case in Indonesia in particular. Since this country is considered to be the largest consumption of smoking "kretek" tobacco, it is clear that smoking already becomes ‘tradition’ among Indonesian society. So, the research question for this paper is how the government and local agencies make their efforts to prevent their own people to reduce the habit of smoking. By collecting, studying, reviewing some of the historical literatures and research articles, it shows that there is government's efforts to reduce the behavior of smoking among the people, especially the male ones. But, it doesn't provide great impacts for the people because the government only limits wiggle room of tobacco-advertisement industries, and the tobacco companies are still able to run their business without stricted regulations. Local agencies then are considered to be 'management from below', who also have roles on reducing the habit of usual smoking among the people of Indonesia. Therefore, managing habit of the people doesn't only come from the state-administration, but it can also be the local agencies who have the potential to reduce the 'cultural-tradition' of smoking among the society of Indonesia.